Enhanced efficacy of 3D architectural glass–ceramic scaffolds in vertical bone augmentation compared with conventional bone-block grafts of different origins - Wenjie Wang; Lingling Zheng; Wei Liu; Chunjuan Wang; Dan Chen; Liya Ai; Antonio Apicella; Chao Wang; Yubo Fan (Materials & Design)
To address the challenge of vertical bone augmentation in orofacial surgery and implant dentistry, this study focused on additively manufactured 3D architectural glass–ceramic scaffolds (3DP). The 3DP, which mimics the Haversian canal and trabecular porous structure, was innovatively designed and fabricated using Digital Laser Processing (DLP) additive manufacturing. The morphology, microstructure, elemental composition and mechanical characteristics of 3DP were compared with those of bovine Xenogeneic Bone Block (XBB), human Allogeneic Bone Block (ABH), and rabbit Autogenous Bone Block (ABR). Furthermore, the vertical osteogenic capacity using a rabbit calvarium model were compared among them. Micro-CT and histology analyses revealed that the osteogenic height, volume, and area of 3DP and XBB were superior to those of ABH and ABR, and 3DP demonstrated a more rapid vertical osteogenesis compared to XBB. The excellent vertical osteogenic performance of 3DP should be attributed to the ideal pore size of its microporous structure, the spatial maintaining force of its overall architecture, and its microcrystalline chemical composition after sintering. Moreover, the vertical channels in the porous network seemed to promote the rapid vertical growth of bone tissue at the early stage.